Heart Failure Association of the European Society of Cardiology update on sodium–glucose co‐transporter 2 inhibitors in heart failure. (27th October 2020) - Seferović, Petar M.; Fragasso, Gabriele; Petrie, Mark; Mullens, Wilfried; Ferrari, Roberto; Thum, Thomas; Bauersachs, Johann; Anker, Stefan D.; Ray, Robin; Çavuşoğlu, Yuksel; Polovina, Marija; Metra, Marco; et al.
Abstract : The Heart Failure Association (HFA) of the European Society of Cardiology (ESC) has recently issued a position paper on the role of sodium–glucose co‐transporter 2 (SGLT2) inhibitors in heart failure (HF). The present document provides an update of the position paper, based of new clinical trial evidence. Accordingly, the following recommendations are given: Canagliflozin, dapagliflozin empagliflozin, or ertugliflozin are recommended for the prevention of HF hospitalization in patients with type 2 diabetes mellitus and established cardiovascular disease or at high cardiovascular risk. Dapagliflozin or empagliflozin are recommended to reduce the combined risk of HF hospitalization and cardiovascular death in symptomatic patients with HF and reduced ejection fraction already receiving guideline‐directed medical therapy regardless of the presence of type 2 diabetes mellitus.